Performance during a 20-km cycling time-trial after caffeine ingestion - Bortolotti, Henrique (BioMed Central, 2014)
BACKGROUND: The objective of this study was to analyze the effect of caffeine ingestion on the performance and physiological variables associated with fatigue in 20-km cycling time trials. METHODS: In a double-blind placebo-controlled crossover study, 13 male cyclists (26 ± 10 y, 71 ± 9 kg, 176 ± 6 cm) were randomized into 2 groups and received caffeine (CAF) capsules (6 mg.kg(−1)) or placebo (PLA) 60 min before performing 20-km time trials. Distance, speed, power, rpm, rating of perceived exertion (RPE), electromyography (EMG) of the quadriceps muscles and heart rate (HR) were continuously measured during the tests. In addition, BRUMS questionnaire was applied before and after the tests. RESULTS: Significant interactions were found in power and speed (P = 0.001), which were significantly higher at the end of the test (final 2 km) after CAF condition. A main effect of time (P = 0.001) was observed for RPE and HR, which increased linearly until the end of exercise in both conditions. The time taken to complete the test was similar in both conditions (PLA = 2191 ± 158 s vs. CAF = 2181 ± 194 s, P = 0.61). No significant differences between CAF and PLA conditions were identified for speed, power, rpm, RPE, EMG, HR, and BRUMS (P > 0.05). CONCLUSION: The results suggest that caffeine intake 60 min before 20-km time trials has no effect on the performance or physiological responses of cyclists.